2023
DOI: 10.3390/fib11020015
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Plastic in Consumer Goods: Opportunities for Coarser Wool

Abstract: Production and use of plastic products have drastically increased during the past decades and their environmental impacts are increasingly spotlighted. At the same time, coarse wool, a by-product of meat and dairy production, goes largely unexploited in the EU. This paper asks why more coarse wool is not used in consumer goods, such as acoustic and sound-absorbing products, garden products, and sanitary products. This is answered through a SWOT analysis of results from a desktop study and interviews with produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The environmental cost of wool processing has imposed the discovery of new applications in order to justify the expenditure. Thus, a performed Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis revealed that wool may be used successfully, instead of plastic materials, in many products other than clothes [197].…”
Section: Textile Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental cost of wool processing has imposed the discovery of new applications in order to justify the expenditure. Thus, a performed Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis revealed that wool may be used successfully, instead of plastic materials, in many products other than clothes [197].…”
Section: Textile Productsmentioning
confidence: 99%
“…Concerning the sustainable aspects of wool valorization and the prospects of wool for replacing plastic materials, we have taken into consideration the advantages and disadvantages of such replacement (see Table 3) [197]. As listed in Table 3, wool has many qualities useful for successfully challenging the use of plastics, and, for the environment, it would be beneficial if wool at least partially replaced these materials.…”
Section:  Cosmeticsmentioning
confidence: 99%
“…Recycled fibers may also be used for molded fiber products [386]. Animalorigin fibers such as wool are also being researched [387]. Cork-polymer composites with chitosan and PE-graft-maleic anhydride has been studied for its improved mechanical and thermal characteristics, as well as its antibacterial and antifouling properties [388].…”
Section: Biocompositesmentioning
confidence: 99%
“…Cabanes [24], [25]. These studies were conducted only on HDPE and polyethylene imine materials and limited to only virgin materials.…”
Section: Introductionmentioning
confidence: 99%